Efektivitas Penggunaan Video Animasi 3D melalui Model PBL terhadap Hasil Belajar Materi Sistem Pernapasan Manusia - Wiwik Apriliya; Fina Fakhriyah; Khamdun Khamdun (FONDATIA, 2026)
The low IPAS learning outcomes of Grade V students at SDN Purwokerto on the abstract topic of the human respiratory system, the limited use of contextual learning media, and the continued dominance of conventional teaching practices form the background of this study. This research aimed to analyze the difference in learning outcomes before and after the implementation of 3D animation videos through a Problem Based Learning (PBL) model and to measure its effectiveness. A quantitative approach was employed using a pre-experimental one-group pretest–posttest design involving 20 Grade V students. Data were collected through learning achievement tests, observation, and documentation, and were analyzed using a paired-sample t-test and N-Gain analysis. The results show an increase in the mean score from 51.4 on the pretest to 87.3 on the posttest, with the paired-sample t-test indicating a significant difference (p < 0.001) and an N-Gain score of 0.7451, categorized as high. These findings demonstrate that the use of 3D animation videos through the PBL model is effective in improving students’ IPAS learning outcomes on the human respiratory system topic. The study concludes that the application of 3D animation videos based on Problem Based Learning is not only effective in enhancing IPAS learning outcomes in elementary schools but also contributes to the development of technology-based IPAS instruction and provides recommendations for the systematic implementation of 3D visual media in contextual learning.